2004
DOI: 10.1029/2003rs002971
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wave fields by Fourier integral operators and their application for radio occultations

Abstract: [1] Fourier integral operators (FIOs) are used for constructing asymptotic solutions of wave problems and for the generalization of the geometrical optics. Geometric optical rays are described by the canonical Hamilton system, which can be written in different canonical coordinates in the phase space. The theory of FIOs generalizes the formalism of canonical transforms for solving wave problems. The FIO associated with a canonical transform maps the wave field to a different representation. Mapping to the repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 24 publications
0
158
0
Order By: Relevance
“…These methods allow enhancing the retrieval accuracy and resolution (e.g., Gorbunov and Gurvich, 1998a, b;Gorbunov, 2002a;Gorbunov and Lauritsen, 2004) as well as obtaining new information on the structure of the atmosphere (Pavelyev et al, 2012, 2015, andreferences therein). In particular, Pavelyev et al (2015) demonstrated the potential of the locality principle for the localization and estimation of the parameters of layered structures as well as the separation of the contributions of layered structures and turbulence in RO signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods allow enhancing the retrieval accuracy and resolution (e.g., Gorbunov and Gurvich, 1998a, b;Gorbunov, 2002a;Gorbunov and Lauritsen, 2004) as well as obtaining new information on the structure of the atmosphere (Pavelyev et al, 2012, 2015, andreferences therein). In particular, Pavelyev et al (2015) demonstrated the potential of the locality principle for the localization and estimation of the parameters of layered structures as well as the separation of the contributions of layered structures and turbulence in RO signals.…”
Section: Discussionmentioning
confidence: 99%
“…We position the phase screen in the plane crossing the Earth's center and perpendicular to the incident rays. The occultation geometry has been discussed in many papers: Vorob'ev and Krasil'nikova (1994), Ware et al (1996), Gorbunov and Lauritsen (2004), Cornman et al (2004), and Pavelyev et al (2012), as well as further references therein. The phase screen has been discussed in Hubbard et al (1978), Woo et al (1980), Gurvich (1984), and Gurvich and Brekhovskikh (2001).…”
Section: -D Models Of Refractivity Fluctuation Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…For basic understanding of the retrieval process, we here briefly (Gorbunov, 2002), using a two-parameter fit of background (MSISE-90) to data >40 km combined with a global background search (Lauritsen et al, 2011); background error fixed at 50 %. Optimization after Sokolovskiy and Hunt (1996) with MSISE-90 (>40 km), obs.…”
Section: Ro Data and Processing Descriptionmentioning
confidence: 99%
“…Due to strong refractivity gradients and multipath effects, the GO bending angle retrieval can be inadequate in the troposphere, and therefore wave-optics (WO) algorithms are applied to reconstruct the geometric optical ray structure of the wave field (e.g., Gorbunov, 2002a;Gorbunov and Lauritsen, 2004).…”
Section: Wo Bending Angle Retrievalmentioning
confidence: 99%